Trends in physiotherapy education: retrospective analysis of ECPE presentations - Alves Lopes, António; Almeida, Patrícia; Beenen, Paul (My University, 2012)
The last decade both physiotherapy and education faced many demands. Educators are challenged to show evidence and report their best practices. An overview of what has been the focus in the ECPE conference show and the main areas of interest and the development in the European Higher Education Area. It provides the opportunity to benchmark towards the policy statement of education of the World Physiotherapy Confederation. Thus increase the consistency and perhaps assisting in formulating a relevant research agenda for the future. The purpose of this study is to give an overview of the trends in physiotherapy education of the last decennium as it is presented at the conferences of the European the World Physiotherapy Confederation (ECPE). A descriptive and retrospective study was carried out and qualitative and quantitative analysis was made on the basis of content and study design/ methodology, by 3 independent reviewers of all abstracts presented at each of the two previous ECPE conferences of 2004 (Estoril - Portugal) and 2008 (Stockholm -Sweden). Categories for content analyses were developed on base of the distribution and main themes used in the conference. This analysis was constrainted by lack of transparency on the description of methodologies in the abstracts and also by the different organization of the abstract books. We needed to create a category "Not Conclusive" and make our decisions based on the rahter classic distinction of qualitative and quantitative study types and methodology. In the results we can find an increase of total presentations from the first to the second conference. In both conference there is a clear preference for special interest issues and in the research the qualitative studies are more favored. There is a total increase in research and implementation research from the first conference to the second. We intepretate this as a logical consequence as in the first conference most of the presentations were focused on new strategies and policies. In the second conference the aim was more directed to the implementation and scientific grounding of these innovations. Educations Institutes and professionals developed more research on Continuous Professional Development, Teaching and Learning strategies, Curriculum Development and Clinical Education. Presumably these topics are related with the European movement – ‘ Europe a strong society in 2020!’, where education and professionals should meet an European standard. The next step could be a comparison with WCPT and educational networks like COHEHRE and ENPHE. It helps researchers and educators to get a better inside of the research agenda and build upon earlier work. It gives an incentive to the development of high quality methodologies. An overview of reports in conferences gives the opportunity to compare with published results and could challenge publishing criteria.